Challenges in Implementing Community-Based Healthcare Teams in a Low-Income Country Context: Lessons From Ethiopia's Family Health Teams - Teralynn Ludwick; Misganu Endriyas; Alison Morgan; Sumit Kane; Margaret Kelaher; Barbara McPake (Kerman University of Medical Sciences, 2022)
Background  Addressing chronic diseases and intra-urban health disparities in low- and middle-income countries (LMICs) requires new health service models. Team-based healthcare models can improve management of chronic diseases/complex conditions. There is interest in integrating community health workers (CHWs) into these teams, given their effectiveness in reaching underserved populations. However healthcare team models are difficult to effectively implement, and there is little experience with team-based models in LMICs and with CHW-integrated models more generally. Our study aims to understand the determinants related to the poor adoption of Ethiopia's family health teams (FHTs); and, raise considerations for initiating CHW-integrated healthcare team models in LMIC cities. Methods  Using the Consolidated Framework for Implementation Research (CFIR), we examine organizational-level factors related to implementation climate and readiness (work processes/incentives/resources/leadership) and systemlevel factors (policy guidelines/governance/financing) that affected adoption of FHTs in two Ethiopian cities. Using semi-structured interviews/focus groups, we sought implementation perspectives from 33 FHT members and 18 administrators. We used framework analysis to deductively code data to CFIR domains. Results  Factors associated with implementation climate and readiness negatively impacted FHT adoption. Failure to tap into financial, political, and performance motivations of key stakeholders/FHT members contributed to low willingness to participate, while resource constraints restricted capacity to implement. Workload issues combined with no financial incentives/perceived benefit contributed to poor adoption among clinical professionals. Meanwhile, staffing constraints and unavailability of medicines/supplies/transport contributed to poor implementation readiness, further decreasing willingness among clinical professionals/managers to prioritize non-clinic based activities. The federally- driven program failed to provide budgetary incentives or tap into political motivations of municipal/health centre administrators.   Conclusion  Lessons from Ethiopia's challenges in implementing its FHT program suggest that LMICs interested in adopting CHW-integrated healthcare team models should closely consider health system readiness (budgets, staffing, equipment/medicines) as well as incentivization strategies (financial, professional, political) to drive organizational change.